MENINGKATKAN EFESIENSI BIAYA DISTRIBUSI SEPATU OLAHRAGA DENGAN MENGGUNAKAN MODEL LOGISTIC STEPPING STONE - Aron Micael Tambunan; Aldy Putra Puji Siswoko, Muhamad Arkan Deni Friansiah, Paduloh (ADISAM PUBLISHER, 2024)
Improving shipping cost efficiency is a significant issue in the distribution of sports shoes at the wholesale level, such as Pak Sumitro in Bekasi. Sports shoes are supplied from Cikarang, Cibitung, and Karawang, stored in Kranji, Jati Waringin, and Jatiwarni warehouses, and distributed to Sumarecon Mall, Pondok Gede Mall, and Kalimalang Mall using pick-up trucks. The Northwest Corner (NWC) transportation model is used to optimize shipping costs. The initial step is to determine the shipping cost from the warehouse to the mall, the total collected is in the warehouse as well as the demands for sports shoes in each mall. The calculation of the cost of shipping sports shoes from three warehouses to three malls using the NWC model shows a cost of IDR 167,500. However, with the Stepping Stone method, the optimal solution shows transportation costs to be IDR 147,500, thus saving shipping costs of IDR 20,000. This research succeeded in finding a solution to optimize the shipping costs of sports shoes, providing economic benefits for traders like Pak Sumitro.